IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN HALMAHERA UTARA - Mokola, Yiska Juniarti; RUMAPEA, PATAR; ROMPAS, SONNY (Sam Ratulangi University, 2014)
This research was carried out by focusing the discussion on the problem ofpolicy implementation in the public service population and civil registry offices in NorthHalmahera Regency in making ID cards. This study aimed to determine how the implementationof public service policy has been conducted in the department of population and civil registrationdistrict of North Halmahera in terms of ID cards, and to help authors understand how theimplementation of the pubic service policy is applied in the sphere of local government,particularly the official residence and recording civil.This research was conducted using qualitative research methods in the Department ofPopulation and Civil Registration, the Government of North Halmahera, North Malukuprovince the number of respondents is as much as 10 employees in the Department ofPopulation and Civil Registration District of North Halmahera. The technique used to performdata collection is observation Participation (participan Observation), in-depth interviews (indepth interviews), and study documentation. Data analysis techniques used in qualitativeresearch is a model of Miles and Huberman. Based on the research conducted, it is known thatthere are objective or objectives are clear and consistent policy regarding the ID card in theoffice of population and civil registration district of North Halmahera; There is strongtheoretical support in formulating policy ID card at the Office of Population and CivilRegistration District of North Halmahera; law foundation policy implementation process ofpolicy-making government-issued ID card at the Office of Population and Civil RegistrationDistrict of North Halmahera which ensures compliance of the employees in the Department ofPopulation and Civil Registration in North Halmahera district to collect data of ID cards; Thereis a good commitment from the employee to perform the tasks in the success of local governmentprograms in the field of Population and Civil Registration; There is support from stakeholdersas well as the entire community in supporting the Office programs to create an orderly society interms of administration; and support the development of social, economic and political in aneffort to prosperity.Keywords: Implementation, Public Services Policy, Office of Population and Civil Registration